Genetically distinct hantaviruses in two bat species in Panamá - Yamada, Karen; Kikuchi, Fuka; Dunnum, Jonathan L.; Gutiérrez-Moreno, Pablo; González D., Publio E.; Armién, Blas; Pérez-Callejas, Mihail; Land, Danielle; Colella, Jocelyn P.; Mizutani, Tetsuya; Maeda, Ken; Suzuki, Motoi; et al. (iScience, 2025)
Recent discoveries of hantaviruses in bats in Europe, Asia, and Africa have prompted expanded explorations of their host diversity and geographic distribution. In screening lung tissue of 218 bats from Panamá, representing 19 genera and five families, we detected hantavirus RNA in two of three greater sac-winged bats (Emballonuridae: Saccopteryx bilineata) and in four of 29 Seba’s short-tailed bats (Phyllostomidae: Carollia perspicillata). Phylogenetic analyses of the small, medium, and large genomic segments revealed a newfound hantavirus in S. bilineata, tentatively designated Filo del Tallo virus, and the recently reported Buritiense virus in C. perspicillata. Both share common ancestry with bat-associated hantaviruses in Asia and Africa. These results indicate that bats serve as hosts of hantaviruses in the Americas. Given opportunities for close contact between humans and bats, studies on the genetic diversity, pathogenicity, and circulation dynamics of hantaviruses are urgently needed. [Display omitted] •Bat-borne hantaviruses were discovered in Central America•A distinct hantavirus was detected in an emballonurid bat species in Panamá•A Brazilian hantavirus was detected in the same phyllostomid bat species in Panamá Virology; Zoology; Microbiology